2021
DOI: 10.2196/21638
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impacts, Acceptability, and Recommendations for Ecological Momentary Assessment Among Youth Experiencing Homelessness: Qualitative Study

Abstract: Background The use of ecological momentary assessment (EMA) to study youth experiencing homelessness (YEH) behaviors is an emerging area of research. Despite high rates of participation and potential clinical utility, few studies have investigated the acceptability and recommendations for EMA from the YEH perspective. Objective This study aimed to describe the perceived benefits, usability, acceptability, and barriers to the use of EMA from the homeless… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(75 reference statements)
1
11
0
Order By: Relevance
“…The study’s implications include support for using intensive longitudinal methods such as EMA with housed and unhoused young adults. Acorda et al [ 26 ] explored the impact and acceptability of EMA among 18 youths experiencing homelessness, making recommendations for use with young people who are actively homeless. The results produced by Acorda et al [ 26 ] reinforce the findings of this study, most notably the effects of increased self-awareness and the potential for behavior change as a result of EMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study’s implications include support for using intensive longitudinal methods such as EMA with housed and unhoused young adults. Acorda et al [ 26 ] explored the impact and acceptability of EMA among 18 youths experiencing homelessness, making recommendations for use with young people who are actively homeless. The results produced by Acorda et al [ 26 ] reinforce the findings of this study, most notably the effects of increased self-awareness and the potential for behavior change as a result of EMA.…”
Section: Discussionmentioning
confidence: 99%
“…Acorda et al [ 26 ] explored the impact and acceptability of EMA among 18 youths experiencing homelessness, making recommendations for use with young people who are actively homeless. The results produced by Acorda et al [ 26 ] reinforce the findings of this study, most notably the effects of increased self-awareness and the potential for behavior change as a result of EMA. Given the discussion regarding perceived behavioral change and behavioral intentions, EMA also presents possible opportunities for intervention work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer recall periods, such as those occurring over 30 days, may not provide granular detail on behavior that occurs more frequently or feeling states that change throughout a single day. Research with other vulnerable unstably housed populations, such as homeless young adults (Acorda, Businelle, and Santa Maria, 2021;Linnemayr et al, 2021) has found EMA to be acceptable and feasible, yet we are not aware of any study that has examined the acceptability and feasibility of phone-based EMA with VEH.…”
Section: Background and Motivationmentioning
confidence: 98%
“…While our main study collected longitudinal data on a monthly basis, measurement points for certain variables such as emotional states or mental health symptoms could be considered infrequent and affected by recall biases. EMA is a sampling strategy that can leverage the ubiquity of smartphone technology to measure behavior in the moment, thus improving ecological validity (Acorda, Businelle, and Santa Maria, 2021;. EMA is especially well suited to study aspects of daily life including affect, hunger, sleep, and psychological distress.…”
Section: Background and Motivationmentioning
confidence: 99%